Understanding matrix structures and their alternatives : the key to designing and managing large, complex organizations - Egelhoff, William G., 1941-; Wolf, Joachim (Palgrave Macmillan, 2017)
This book describes the use of matrix structures in large, complex organizations such as MNCs. Using an information-processing perspective of organization design, it develops a more comprehensive theory for fitting the structural configurations of matrix structures to key characteristics of firm strategy. Empirical research by the authors supports this theoretical framework. In addition to structural configuration, Understanding Matrix Structures identifies and develops the mode of decision making within a matrix as an important second dimension of matrix structure design. It can be either balanced (joint) decision making by the two dimensions of a matrix or rule-based decision making, where rules pre-assign certain decisions to one dimension or the other for unitary decision making. Recent exploratory research by the authors supports this conceptual framework and provides the potential to create a more flexible matrix structure- one that facilitates a more ambidextrous organization.
Keywords: Matrix organization.; Management.; elektronické knihy; electronic books